Nanoaluminium: Is There any Relationship betweenParticle Size, Non-isothermal Oxidation Data andBallistics?; Central European Journal of Energetic Materials; Vol. 14, iss. 3 - Gromov A. A. Aleksandr Aleksandrovich (2017, 2017)
Title screen